The Constitution of the Republic of the Philippines Explained - Nolledo, Jose N. (Mandaluyong City, 2005)
This edition was updated to include leading cases on the Constitution up to July, 2005. There have been substantive rulings by the Supreme Court which were cited in this edition such as those relating to the expropriation process and the pay-ment of just compensation, the allowance of DNA testing in paternity cases without violating the right to privacy and the right against self-incrimination, the fiscal au-tonomy of the Civil Service Commission, and the upholding of financial and techni-cal assistance agreements under the Mining Act.
Keywords: Constitutional Law-- Philippines